A Comparative Study Between Cefixime and Ofloxacin in The Treatment of Uncomplicated Typhoid Fever Attending A Tertiary Care Teaching Hospital - Mishra, Chandan; Jha, Awadhesh Kumar; Ahmad, Md. Parwez; Singh, Smita; Ansari, Akhtar Alam (Med Phoenix, 2017)
Background: Typhoid fever is a gastrointestinal infection caused by Gram-negative bacterium Salmonella enterica serovar typhi (S.typhi). Typhoid fever continues to be one of the major public health problems in developing countries. Antimicrobial therapy is critical for the clinical management of enteric fever. Incidences of multi-drug resistance to S. typhi (MDRST) and nalidixic acid resistant (NAR) strain have limited treatment options. Resistance pattern and time to fever clearance vary in different geographical areas and overtimes. Hence, this study was conducted to compare efficacy and safety profile of Cefixime and Ofloxacin in uncomplicated typhoid fever in this region. Method: 50 adults proven cases of typhoid fever of the age group of 18-57 years of either sex were included in the study. Group I was treated with Cefixime 200 mg twice a day for 7 days and CG I was treated with Ofloxacin 200 mg twice a day for 7 days. Patients were clinically and bacteriologically evaluated during the study period and follow-up. Result: So both study groups were found comparable in terms of mean fever clearance time. 96% cure rates were observed in both groups. No relapse was recorded. Conclusion: Both Cefixime and Ofloxacin are equally efficacious and safe in the treatment of uncomplicated typhoid fever. Med Phoenix Vol.2(1) July 2017, 3-7